Mean performance and heritability studies of some ridge gourd (Luffa acutangula L.) genotypes - Methela, Nusrat Jahan; Islam, Mohammad Shafiqul; Mitu, Nazmunnahar; Latif, Md Abdul (Research in Agriculture Livestock and Fisheries, 2019)
In the present investigation, 29 genotypes of ridge gourd were grown during 2016-2017 at the experimental field of Regional Horticulture Research Station, Patuakhali, Bangladesh. The experiment was laid out in randomized complete block design with three replications. The mean sum of squares is due to various sources of variance for different characters of ridge gourd genotypes. The results indicated highly significant variation among the genotypes for the 11 characters studied viz., such as fruit length, fruit diameter, single fruit weight, number of fruits per plant, yield of fruit per plant. The genotype BD2975 showed the highest performance in fruit length (42.05cm) and weight of fruits (258.90g). While the genotype PK3 showed the highest performance in number of fruits per plant (28.67), respectively. Of eleven traits, eight showed high heritability (over 80%). The highest genotypic and phenotypic coefficients were recorded in the parameter fruit yield per plant (39.59% and 40.96%). Res. Agric., Livest. Fish.6(1): 45-55, April 2019